Sport Concussion Assessment Tool-5th Edition (SCAT5): Normative Reference Values for the National Rugby League Women's Premiership - Iverson, Grant L.; Howell, David R.; Van Patten, Ryan; Bloomfield, Paul; Gardner, Andrew J. (Frontiers in Sports and Active Living, 2021)
Objective: To establish normative reference values for the Sport Concussion Assessment Tool-5th Edition (SCAT5) for the new National Rugby League Women's Premiership. Methods: Preseason SCAT5 baseline testing was administered individually to all National Rugby League Women's Premiership players (N = 117). Testing was completed by the medical staff. Normative reference values were calculated for the components of the SCAT5, including the Standardized Assessment of Concussion, modified Balance Error Scoring System, and the Symptom Scale. A small case series of players who sustained concussions were included to illustrate the use of the new normative data. Results: The median Standardized Assessment of Concussion total score was 27.0 (M = 26.9, SD = 2.1). The median modified Balance Error Scoring System score was 2.0 (M = 2.4, SD = 2.2). The median number of symptoms score was 1.0 (M = 3.2, SD = 4.7) and the median symptom severity score was 2.0 (M = 5.4, SD = 8.2). The most common baseline symptom was fatigue or low energy (33%), followed by trouble sleeping (24%), headache (23%), neck pain (22%), and difficulty remembering (21%). In the total sample, 41% reported no symptoms. The clinical interpretation of these new normative data to a case series of women with concussions is provided. Conclusions: Normative reference values are provided for the SCAT5 for women who are professional rugby league players. Using these normative data will improve clinical interpretation of SCAT5 scores following a concussion.